Formulation and In vitro Characterization of Metformin HCl Hibiscus rosa sinensis Mucilage Controlled Release Matrix Tablets - Soujanya, C. (International Journal of Pharmaceutical & Biological Archive, 2022)
Introduction: Controlled release drug delivery systems have received much attention in the past two decades with numerous technologically sophisticated products on the market place. Such advancements have come about by convergence of many factors, including the discovery of novel polymers, formulation optimization, better understanding of physiological and pathological constraints, prohibitive cost of developing new drug entities, and the introduction of biotechnology and biopharmaceutical principles in drug product design. The major benefits of these products lie in the optimization of drug input rate into the systemic circulation to achieve an appropriate pharmacodynamic response. Materials and Methods: The drug metformin hydrochloride was selected taking into consideration of their physiochemical, biopharmaceutical properties, and rationale of clinical efficacy. It is an oral hypoglycemic agent; chemically it is 1, 1–dimethyl biguanide derivative, acts by suppressing hepatic gluconeogenesis. It is a white, crystalline powder, and hygroscopic in nature. It is freely soluble in water and slightly soluble in alcohol, practically insoluble in acetone and in dichloromethane. Metformin HCl is readily absorbed from the gastrointestinal tract, having oral bioavailability of 50–60%, peak plasma concentration (Cmax) is reached within 1–3 h with immediate release and 4–8 h with extended release. Plasma protein binding of Metformin HCl is negligible, as reflected by its very high apparent volume of distribution (300–1000 Lit after a single dose). Metformin HCl is not metabolized and excreted as unchanged form in urine, having elimination half-life of 2–6 h. Results: In the present work, the rate of dug release can be prolonged using polymer matrix system, which influences the intragel swelling dynamics and relative physical integrity of the swollen matrix structure. Conclusion: Furthermore, that may produce heterogeneous domains within the swollen gel boundary.